Pré-hidrólise ácida de bagaço de cana-de-açúcar e sua caracterização físico-química - Morais, Alaíne Patrícia da Silva [UNESP] (2012)
The biomass resulting from processing sugarcane bagasse has been considered a source of cellulose with the potential production of bio-fuels. This lignocellulose can be processed into ethanol since is hydrolyzed by chemical processes (acids) or biotechnology (enzymes) which generate sugars suit for fermentation. This study had the objective to utilize physical and chemical pre-treatment processes for prehydrolysis of sugarcane bagasse. The experimental treatment was adjusted at a factor of 4 X 2, by the combination of pre-hydrolysis timing (15, 30, 45 and 60 minutes) and sulfuric acid concentrations (7.0% and 9.0%) which was incubated at a temperature of 121° C in an autoclave. The treatment data was subjected to analysis of the variance and averages which were compared using the Tukey test with a probability of 5%. The results obtained showed that through pretreatment acid applied on the lignocellulose material, there was a significant break from the substrate fibers like cellulose, hemicellulose and lignin.